1988
DOI: 10.1093/ajcn/47.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Iron status of premenopausal women in a university community and its relationship to habitual dietary sources of protein

Abstract: Dietary intake and iron status was evaluated in 52 nonpregnant premenopausal women who were not using Fe supplements. Subjects were separated into three groups based on their habitual consumption of red meat (RM), fish and/or poultry (FP), or lacto-ovovegetarian (LV) sources of protein. No differences were observed among the groups in demographic characteristics (eg, age, height, weight, reported number of menstrual days per year) or total Fe intake. However, those women consuming red meat as their predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 0 publications
5
38
0
1
Order By: Relevance
“…The increase of Hgb and Hct in the beef group once meat, in the form of beef, was re-introduced to the beef group suggests that there may have been some change in erythropoiesis or expression of erythropoiesis with the transition to a beef-containing diet. The increased Hgb and Hct noted when subjects consumed beef is similar to the findings of Ortega and colleagues (23) and WorthingtonRoberts and colleagues (24). In a study of young women, Ortega and colleagues (23) found higher levels of Hgb and Hct in those who consumed ≥100 g (3.5 oz) of meat per day.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increase of Hgb and Hct in the beef group once meat, in the form of beef, was re-introduced to the beef group suggests that there may have been some change in erythropoiesis or expression of erythropoiesis with the transition to a beef-containing diet. The increased Hgb and Hct noted when subjects consumed beef is similar to the findings of Ortega and colleagues (23) and WorthingtonRoberts and colleagues (24). In a study of young women, Ortega and colleagues (23) found higher levels of Hgb and Hct in those who consumed ≥100 g (3.5 oz) of meat per day.…”
Section: Discussionsupporting
confidence: 78%
“…In a study of young women, Ortega and colleagues (23) found higher levels of Hgb and Hct in those who consumed ≥100 g (3.5 oz) of meat per day. Worthington-Roberts and colleagues (24) found that young women whose habitual predominant source of protein came from red meat had greater Hgb and Hct concentrations than women whose predominant source of protein was fish and poultry or lacto-ovo vegetarian.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were seen in total iron intake but those women consuming red meat as their predominant source of protein demonstrated superior iron status, especially reflected by higher serum ferritin concentrations. These authors concluded that the form rather than the amount of dietary iron appeared to be most influential on iron status 32 . Another study divided young Spanish women on the basis of their meat consumption (above or below 100 g day 21 ) and concluded that because high meat consumers showed higher levels of Hb, restriction of meat and meat products could have negative repercussions on the nutritive status and health of certain groups within the population, particularly young females 33 .…”
Section: Considerations Of Assumptions Made In Our Studymentioning
confidence: 99%
“…Meat consumption is associated with higher iron status in women (45); this is probably related in part to slightly higher intakes of iron by meat eaters and the higher bioavailability of heme than nonheme iron. We suggest that it might also be related to higher stearic acid consumption by meat eaters than by women who eat predominantly fish and poultry or who are lactoovo vegetarians.…”
Section: Discussionmentioning
confidence: 99%